Maize zinc uptake is influenced by arbuscular mycorrhizal symbiosis under various soil phosphorus availabilities - Yu, Baogang (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.